2022
DOI: 10.1111/evo.14563
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic emergence and modulation of sex‐specific dominance reversals in threshold traits

Abstract: Sex‐specific dominance reversals (SSDRs) in fitness‐related traits, where heterozygotes' phenotypes resemble those of alternative homozygotes in females versus males, can simultaneously maintain genetic variation in fitness and resolve sexual conflict and thereby shape key evolutionary outcomes. However, the full implications of SSDRs will depend on how they arise and the resulting potential for evolutionary, ecological and environmental modulation. Recent field and laboratory studies have demonstrated SSDRs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 82 publications
(362 reference statements)
0
6
0
Order By: Relevance
“…Because such dominance relationships may result from fitness landscapes declining slowly away from phenotypic optima (i.e. showing diminishing returns to adaptation [37], as found on Gaussian fitness landscapes), multiple authors have suggested that favourable conditions for sexually antagonistic polymorphism may be common, especially in well-adapted populations [5,10,14,15,30,[38][39][40][41][42][43] (where landscapes typically show diminishing returns [44,45]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because such dominance relationships may result from fitness landscapes declining slowly away from phenotypic optima (i.e. showing diminishing returns to adaptation [37], as found on Gaussian fitness landscapes), multiple authors have suggested that favourable conditions for sexually antagonistic polymorphism may be common, especially in well-adapted populations [5,10,14,15,30,[38][39][40][41][42][43] (where landscapes typically show diminishing returns [44,45]).…”
Section: Introductionmentioning
confidence: 99%
“…One salient point from this theory is that sexual antagonism can maintain a balanced genetic polymorphism for two alleles at a locus either when selection is strong and symmetrical between the sexes, or when allelic dominance is sex-specific such that alleles are more dominant when beneficial and more recessive when deleterious ("sex-specific dominance reversal" [18,23,30]). Because such dominance relationships can result from fitness landscapes declining slowly away from phenotypic optima (i.e., showing diminishing returns to adaptation [37,38]), it has been suggested that sexually antagonistic balancing selection may be common, especially in well-adapted populations [5,10,23,30,[38][39][40][41][42][43][44]. Furthermore, even when sexually antagonistic polymorphism is not balanced and therefore ephemeral, it may nevertheless persist for longer than other non-neutral variation due to opposing selection in males and females [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The degree to which the evolution of dominance is constrained has been a matter of some debate (Otto and Bourguet, 1999;Grieshop et al, 2024), but it is clear that sex-specific dominance for phenotypic traits could emerge either through nonlinearities in the manner in which allelic effects are translated into phenotypes (Wright, 1934;Kacser and Burns, 1981;Otto and Bourguet, 1999;Reid, 2022) or through dominance modifiers (Spencer and Priest, 2016;Grieshop et al, 2024). Second, unlike previous theory studying the implications of sex-specific dominance, our model is not restricted to BAP.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that we observe sex-specific dominance emerging in our model is, although consequential, perhaps not surprising: the evolution of adaptive dominance is predicted when polymorphism is maintained by marginal overdominance, as this increases heterozygote fitness (Fisher, 1931). The degree to which the evolution of dominance is constrained has been a matter of some debate (Otto and Bourguet, 1999; Grieshop et al, 2024), but it is clear that sex-specific dominance for phenotypic traits could emerge either through nonlinearities in the manner in which allelic effects are translated into phenotypes (Wright, 1934; Kacser and Burns, 1981; Otto and Bourguet, 1999; Reid, 2022) or through dominance modifiers (Spencer and Priest, 2016; Grieshop et al, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Note, however, that trait-level dominance reversals may or may not be dominance reversed for fitness, per se , depending on how the phenotype maps to fitness. In principle, dominance reversals at the phenotypic level could occur due to traits being threshold-like (non-linear genotype–phenotype relationship) [ 103 ], or could arise due to the explicit action of a dominance modifier [ 62 ].
Figure 1 Graphical representation of beneficial dominance reversals.
…”
Section: Evolutionary Causes Of Dominance Reversalsmentioning
confidence: 99%